Rights of Women with Mental Illness (WWMI): Nigeria in Context - Ayantunde Ayankola; Damilola Olabanji; Omotola Ogunjobi; Toyosi Kayode Olabanji (Journal of Women's Mental Health, 2023)
Introduction This study addresses the critical issue of the rights of Women with Mental Illness (WWMI) in Nigeria, emphasizing the intrinsic link between mental health and human rights. Recognizing the unique challenges faced by women, particularly those with mental health conditions, is essential for achieving global goals related to well-being and gender equality. The aim of the study was to explore the rights of women with mental illness in Nigeria, factors that may be responsible for the difficulty in ensuring that the rights of women with mental illness in Nigeria are protected, and then provide policy suggestions to combat the highlighted challenges. Method A comprehensive literature review was conducted, utilizing databases such as PUBMED, Google Scholar, and African Index Medicus. Key search terms included Women’s rights, Human rights, Mental Health, Nigeria, and UN SDGs. Results The studies selected for the review focused on highlighting the challenges faced in women mental health rights, and identified socioeconomic, traditional and cultural factors as the major challenges to the protection of WWMI. Conclusion The study revealed a complex interplay of societal, cultural, and economic factors contributing to the abuse of rights among WWMI in Nigeria. However, to begin to resolve these challenges, it proposed the need to visibly increase female representation in policy-making, enhance mental health access, and target research efforts. Addressing these issues is crucial for upholding the fundamental human rights of WWMI, ultimately leading to improved mental well-being within society.
Keywords: sustainable development goal (SDG)